Financial Illiteracy and customer credit history - Santos, Danilo Braun (2020)
Purpose – We study how financial illiteracy affects the probability of a derogatory mark on the customer’s credit history. Design/methodology/approach – We use the National Survey on Financial Inclusion in Brazil together with information on financial instrument usage and spending provided by the head of the household. To estimate the impact of financial illiteracy on the probability of a derogatory mark we use a logistic model to compute the odds ratio. Findings – Our main result is that financially illiterate individuals have between 57% and 143% more chance of having a derogatory mark. We find that age, income, expenses, and retirement positively affect the probability of a derogatory mark, while marriage has a negative impact. Gender does not have any impact over the probability of derogatory mark. Originality/value – The study uses a new proxy for financial illiteracy and correlates it to the investment and debt decisions of a family using a unique dataset.